Analisis Efektivitas Pelaksanaan Program Raskin Di Kota Bandar Lampung - Emalia, Zulfa (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 1, Februari 2013 (pp. 1-70))
Subsidized rice which was distributed for the poor has a main purpose to reduced the RTM, it was an action of the Government toward food fulfillment of the poor people, and also decreased the expenditure of RTM. The data used in this research was secondary data, and located at Bandar Lampung in 3 samples sub-distric: Kedaton, Sukarame, and Rajabasa. The method which used to analyze was based on the government rules, which content the affectivity on target, on numbers, on price, on quality, on administration, and on time. The result showed the all content were succeed to echieve except on the numbers, this condition was caused by the addition of the “raskin” volume from 13 Kg/RTM to 15 Kg/RTM.
Keywords: raskin program , poor people , affectivity , RTM , RPJM